PERLINDUNGAN HUKUM TERHADAP JABATAN NOTARIS ATAS DUGAAN PELANGGARAN KODE ETIK DALAM PENGURUSAN HARTA WARIS (STUDI PUTUSAN MAJELIS PENGAWAS PUSAT NOTARIS NOMOR 03/MPPN/VIII/2016) - Michael Amsal Sumitro; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2018)
Notary Is a Public Official granted authority by the State in making an Authentic Deed. On that basis, it is necessary to have legal protection for a Notary if in conducting his / her position of office sued on the alleged violation of code of ethics as it happened in Decision of Supervisory Board of Notary Center Number 03/MPPN/VIII/2016. Notary LIS is sued with alleged violation of code of ethics on the management of the heirs but the allegations according to the judges in both MPW and MPPN the action does not violate the code of ethics. Based on the analysis result that referring to Article 9 paragraph (7) Notary Code of Ethics, the legal protection of the notary's office on the alleged violation of the code of ethics in the management of the permanent inheritance shall be entitled to the protection of a good name through a letter issued by the Notary Publicity Council. The qualification of a notary act can be regarded as a violation of the code of ethics only stipulated in the provisions of Article 4 of the Code of Ethics of 2015. Notary LIS is in fact violating Article 52 UUJN because in carrying out the task of handling of inheritance based on an oral testament there is still family relation. However, the MPPN is not careful that such action is not a violation of UUJN.